Between the trees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Site Management and Productivity in Tropical Forest Plantations. A Tiarks, EKS Nambiar, C Cossalter. Workshop proceedings, 16 20 February 1998, South Africa. CIFOR. Occasional Paper No. 16. 1999. 76 pp. ISBN 979 8764 331. J Manangkil, CIFOR Communic